Swelling kinetic behavior of biochar-graft superabsorbent polymer composites - N., Noordin; S., Jamari; S., Ghazali (Institute of Physics Publishing, 2020)
Superabsorbent polymers (SAPs) are crosslinked three dimensional structures that poses high swelling capacity in aqueous medium. Its application in agriculture beneficial as it is able to retain moisture in soil. SAPs incorporated with bio-char have been prepared via solution polymerization of polyacrylic acid with co-monomer of polyacrylamide in the presence of bio-char using methylenebisacryalmide (MBA) as a crosslinking agent and ammonium persulfate (APS) as an initiator. In this research, the swelling kinetic behavior of SAP with biochar was studied on the effect of biochar percentage loading from 0-0.8wt. SEM imaging of sap icorporated biochar shows a porous structure which influences water absorbency. The maximum of water absorbency capacity reached an optimum value of 129.89 g/g at 0.4 % before decreasing with increasing bio-char loading. Mathematical model of kinetic diffusivity also revealed that the SAP-biochar incorporated follows a second order kinetic. The presence of bio-char could enhance physical properties by increasing the water-holding capacity, enhancing its water absorbency ability. Application of SAP incorporated biochar not only able to retain water, it could also help to fertilize agriculture.